A new species of Puddle Frog, genus Phrynobatrachus (Amphibia: Anura: Phrynobatrachidae) from Ghana - Ofori-Boateng, Caleb; Leaché, Adam D.; Obeng-Kankam, Bright; Kouamé, N’goran Germain; Hillers, Annika; Rödel, Mark-Oliver (Zootaxa, 2018)
We describe a new species of Phrynobatrachus from the eastern part of the Upper Guinea forest region, Ghana, West Africa. Morphologically, the new species can be distinguished from all of its congeners by the combination of a slender body, short and pointed snout, a relatively warty dorsum, a black-spotted throat in both sexes, a gular flap in males, a dark spotted chest, a white-greyish venter with occasional blackish spots, rudimentary pedal webbing, none to slightly dilated finger tips and strongly delated toe tips, presence of both inner and outer metatarsal tubercles and absence of a dark face mask, eyelid tubercles and longer dorsal ridges. We collected mitochondrial DNA (mtDNA) sequence data from the 16S rRNA gene to measure the genetic diversity of the new species, and to estimate phylogenetic relationships. The new species is a distinct and monophyletic evolutionary lineage most closely related to Phrynobatrachus gutturosus, P. fraterculus and P. maculiventris. The discovery of this new species highlights that the biodiversity of West African forests is still incompletely known and that the few remaining forests need urgent protection.